Essential Oil Extracted from Cymbopogon citronella Leaves by Supercritical Carbon Dioxide: Antioxidant and Antimicrobial Activities. (2nd January 2019) - Wu, Hong; Li, Jilie; Jia, Yuan; Xiao, Zhihong; Li, Peiwang; Xie, Yixian; Zhang, Aihua; Liu, Rukuan; Ren, Zewen; Zhao, Mengrui; Zeng, Chaozhen; Li, Changzhu
Abstract : To improve essential oil quality, especially to reserve the thermal instability of compounds, supercritical CO2 extraction (SFE) was applied to recover essential oil from Cymbopogon citronella leaves . A response surface methodology was applied to optimize the extraction process. The highest essential oil yield was predicted at extraction time 120  min, extraction pressure 25  MPa, extraction temperature 35°C, and CO2 flow 18  L/h for the SFE processing. Under these experimental conditions, the mean essential oil yield is 4.40%. In addition, the chemical compositions of SFE were compared with those obtained by hydrodistillation extraction (HD). There were 41 compounds obtained of SFE, while 35 compounds of HD. Alcohols and aldehydes were the main compositions in the essential oils. Furthermore, the antioxidant activities and antimicrobial of essential oils obtained by HD and the evaluated condition of SFE were compared. Results showed that the antioxidant activities of SFE oil are better than those of HD. Minimum inhibitory concentrations (MICs) were determined by the microdilution method. Essential oil obtained from SFE and HD exhibited a significant antimicrobial activity against all tested microorganisms. It is confirmed that the SFE method can be an alternative processing method to extract essential oils from Cymbopogon citronella leaves.